2021
DOI: 10.1177/1708538120986294
|View full text |Cite
|
Sign up to set email alerts
|

Critical limb ischemia patients clinically improving with medical treatment have lower neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios

Abstract: Objectives Inflammation is a component in the pathogenesis of critical limb ischemia. We aimed to assess how inflammation affects response to treatment in patients treated for critical limb ischemia using neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocytes ratios (PLR) as markers of inflammation. Methods Patients in a single tertiary cardiovascular center with critical limb ischemia unsuitable for surgical or interventional revascularization were retrospectively identified. Data were collected on medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The current study also demonstrated the usefulness of PLR and SII as diagnostic markers. In the study by Erdogan et al, NLR and PLR were found to reduce in patients with acute limb ischemia who improve with medical treatment [39]. Saskin et al in their study reported that increased NLR and PLR are found to be associated with extremity amputation in acute arterial occlusions [27].…”
Section: Discussionmentioning
confidence: 95%
“…The current study also demonstrated the usefulness of PLR and SII as diagnostic markers. In the study by Erdogan et al, NLR and PLR were found to reduce in patients with acute limb ischemia who improve with medical treatment [39]. Saskin et al in their study reported that increased NLR and PLR are found to be associated with extremity amputation in acute arterial occlusions [27].…”
Section: Discussionmentioning
confidence: 95%
“…NLR levels ≥ 5.25 were also independently associated with 12-month death in patients with CLTI, including those undergoing infra-popliteal percutaneous intervention [ 135 , 173 ]. In a retrospective study on patients with CLTI unsuitable for revascularization and receiving standard pharmacological treatment including low molecular weight heparin, aspirin, statins, iloprost infusion, and a standard pain medication protocol, lower pre-treatment levels of NLR were associated with subsequent improvement in ischemic pain and healed ulcers [ 136 ]. Other authors showed similar findings [ 138 ].…”
Section: The Established Role Of Neutrophils In Peripheral Artery Dis...mentioning
confidence: 99%
“…Therefore, it is reasonable to conclude that the association between NLR/PLR and outcomes in limb ischemia was also U-shaped. If this is the case, the different cut-off values (Youden index) 13 may be caused by the different proportions of patients with low NLR/PLR values in these studies. For instance, the Youden index in the cohort without patients with low NLR/PLR would be much greater than that in a cohort with a high proportion of patients with low NLR/PLR.…”
mentioning
confidence: 95%
“…We read with great interest Dr Erdogan et al’s study, 1 which investigated the predictive value of neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte (PLR) ratios in patients with critical limb ischemia. The major finding is that after adjusting for covariates, both high NLR and PLR were independently associated with no response to treatment.…”
mentioning
confidence: 99%